Grounded Theory in Practice: Reflexivity and Innovative Approaches for Modern Qualitative Studies - Michael Mncedisi Willie (Southeast Asian Journal of Global Trends and Issues in Education, 2026)
Background: Grounded theory remains a key methodology in qualitative research, providing systematic procedures for generating theory from empirical data. However, the expansion of qualitative research contexts, including digital environments, has introduced new methodological challenges related to reflexivity, analytical rigour, and methodological transparency. Objective: This study examined the development of grounded theory methodologies and explored how reflexivity and innovative methodological approaches strengthen research rigour in contemporary qualitative studies. Method: This study employed a methodological review by synthesising seminal and contemporary literature on grounded theory. The analysis focused on major methodological traditions, including Straussian, Glaserian, and constructivist grounded theory, while also examining issues related to coding procedures, theoretical sensitivity, and literature review management. The review further considered methodological adaptations in digital contexts, particularly the integration of netnography. Results: The review shows that grounded theory has evolved into diverse methodological traditions with distinct analytical procedures. Reflexivity, transparency, and methodological flexibility are increasingly recognised as essential for ensuring credibility and rigour in qualitative research. Conclusion: Grounded theory remains a flexible and relevant methodological framework for contemporary qualitative inquiry. Contribution: This study brings together different grounded theory approaches, showing how careful, reflective, and transparent methods can strengthen qualitative research in today’s diverse contexts.